Development of Android-Based Interactive Learning Media to Promote Green Chemistry Principles in Higher Education - Setiawaty, Sri; Imanda, Riska; Fitriani, Henni; Fatmi, Nuraini (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the feasibility of Android-based green chemistry learning media integrated with Smart App Creator, developed to improve students’ cognitive learning outcomes, assess student readiness toward new learning modes, and analyze student responses to the developed media. The research employed a Research and Development (RD) approach adapted from the Borg Gall model combined with the 4-D procedural model, encompassing the stages of define, design, develop, and disseminate. The learning media product was developed in the form of an Android application focusing on green chemistry concepts and designed using the Smart App Creator software. The feasibility of the developed media was evaluated through expert validation and user response assessments. The results of the validation indicated that the media achieved a validity score of 84% and a quality score of 87%, both categorized as “very good.” In addition, student responses toward the use of the learning media were highly positive, reaching 92%, which reflects a high level of acceptance and readiness to adopt technology-based learning. Furthermore, the implementation of the developed Android-based media demonstrated a significant influence on students’ cognitive learning outcomes, with 72% of students achieving learning completeness. Overall, the findings indicate that the Android-based green chemistry learning media integrated with Smart App Creator is feasible, practical, and effective for supporting chemistry learning. This media offers a promising alternative for enhancing cognitive learning outcomes and facilitating the integration of digital technology into chemistry education.